Moisture absorption behavior and adhesion properties of GNP/epoxy nanocomposite adhesives - Kong, Nurziana; Khalil, Nur Zalikha; Fricke, Holger (MDPI, 2021)
In the current work, an attempt has been made to investigate the effect of Graphene Nanoplatelets (GNP) reinforcement to water absorption behavior and mechanical properties of adhesive bonding with epoxy. Epoxy adhesive with various GNP content (i.e., 0.0~2.0 wt%) was utilized to joint aluminum adherend subjected to various immersion periods (i.e., 0~60 days). Subsequently, the effect of GNP reinforcement on water uptake, water absorption rate and tensile shear strength was investigated. Depending on GNP content, two distinct behaviors in water uptake and moisture absorption rate have been observed; specimens with lower GNP content (0.5~1.0 wt%) have demonstrated increased/retention of water uptake and water absorption rate regardless of immersion period. Meanwhile, at higher GNP content (1.5~2.0 wt%), decreased water uptake and water absorption rate are generally observed. At similar GNP content, regardless of immersion periods, water immersed specimens generally demonstrate higher or retention of shear strength when compared to specimens at 0-day immersion period. These observations suggest that the relation between moisture absorption behavior and mechanical properties of GNP-reinforced adhesive with GNP content are rather complex which might be attributed to the interplay of several possible mechanisms.